Adenocarcinoma da próstata estudo anatomopatológico de biopsias ecoguiadas e peças cirúrgicas de prostatectomia radical e correlação com o antígeno prostático específico - Paulo Guilherme de Oliveira Salles (2010)
Introduction: Prostate adenocarcinoma has a high morbidity and mortality. In our country, there are few studies of large series of patients based on clinical and pathological data on localized prostate adenocarcinoma. Moreover, there is no consensus on the sampling of the surgical specimens of radical prostatectomy. To obtain data on these three characteristics and determine correlations among them, this study was conducted. Methods: We studied 1,534 surgical specimens of radical prostatectomy (1,025) and prostate biopsies (509). The specimens were examined in its entirety (550 cases - Group 1) or partially (475 cases - Group 2 -, comparable for age, PSA, clinical stage and Gleason score to cases in Group 1). Prostate biopsies of 509 patients in Group 1 were also evaluated (Group 3). We recorded age, PSA and held detailed description of the pathological findings of Group 1 cases, assessing the Gleason score, the relationship of the tumor with surgical margins, extraprostatic extension, seminal vesicle invasion, perineural and vascular invasion, multifocality, high grade prostatic intraepithelial neoplasia and pathological stage. Group 2 cases were compared to Group 1 cases with respect to the status of surgical margins and extraprostatic extension, to determine the role of sampling of the radical prostatectomy surgical specimen. The findings of the biopsy (Group 3) - topography and Gleason score - were also compared with the findings of the cases in Group 1 to establish associations on the status of surgical margins and extraprostatic extension. We performed univariate and multivariate analysis and determined ROC curves in an attempt to predict information that may assist the surgeon in determining the prognosis of their patients. Results: The mean age of patients in Group 1 was 62.8 years and mean PSA was 6.6 ng / ml. Surgical margins were affected in one third of cases, extraprostatic extension was seen in one quarter of cases and the predominant Gleason score of surgical specimens was 7 (the predominant score of the biopsies was 6).The findings in determining staging pT3 were more frequent in patients over 70 years, with PSA levels greater than 10.0 ng / ml and biopsy Gleason score equal or greater than 7. Univariate and multivariate analysis showed correlations for multifocality, vascular infiltration, perineural invasion, status of surgical margins and extraprostatic extension with the staging. Complete sampling of the radical prostatectomy specimen allowed more reliable detection of compromised surgical margins and extraprostatic disease. ROC curves showed higher sensitivity and specificity of PSA, compared to biopsy Gleason score, to predict the neoplastic involvement of surgical margins and extraprostatic extension of prostate cancer. Conclusions: The clinical and pathological patterns related to prostate adenocarcinoma observed in this study are similar to standards established in the literature. The PSA and biopsy Gleason score, as well as its topography and the number of regions affected by adenocarcinoma on biopsy are variables that allow correlation and prediction of histology and staging. The complete sample of the specimen of radical prostatectomy is superior to partial sample for the determination of surgical margin involvement, extraprostatic extension and pathological stage.